No way out for climate refugees’ asylum applications in court decisions and conventions - Ekşi, Nuray (Medicine, law & society, 2023)
One major consequence of climate change is the migration problem caused by internal and international displacement of people due to environmental disasters. The cross-border effects of climate-induced displacement have naturally sparked novel debates in the field of refugee law, and has created a group of people commonly called ‘climate refugees’. Climate refugees do not necessarily fall within the definition of ‘refugee’ under the 1951 Geneva Convention. While certain states and international organisations, including the UN, approach the situation of climate refugees solely from a security point of view, others see these people as victims of climate-induced disasters. No country is truly willing to share the burden caused by the climate-induced mass migration or address the full extent of this major phenomenon. Moreover, the international agreements on which they base their asylum claims fail to adequately address the circumstances surrounding their requests. Differing opinions have been expressed in academia as to the appropriate protection mechanisms and assistance that can be provided to climate refugees. In article, we explain the differences between the conventional refugees and climate refugees, discuss the reasons why the existing international conventions fail to protect climate refugees, and highlight the proposed solutions for the protection of such refugees.
Keywords: 1951 Geneva Convention; azil; begunci; climate induced migration; climate refugees; environmental refugees; environmentally displaced persons; klimatske spremembe; klimatski begunci; Konvencija o statusu beguncev; mednarodne migracije